Multiparametric assessment of the intraprocedural result after transcatheter mitral valve edge-to-edge repair proceduret. (4th February 2022) - Melillo, F; Colopi, M; Falsasconi, G; Ancona, F; Pannone, L; Stella, S; Ingallina, G; Castiglioni, A; De Bonis, M; Beneduce, A; Godino, C; Buzzatti, N; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Research grant OnBehalf: n/a Background. Quantification of residual mitral regurgitation (MR) after transcatheter edge-to-edge mitral valve repair (TMVr) is challenging. Objectives. To evaluate the feasibility and the performance of an intraprocedural multiparametric approach based on echocardiographic and invasive hemodynamic parameters and to develop a multiparametric scoring system for MR grading after TMVr, and to compare this approach against currently recommended methods. Methods. Ninety-three consecutive patients treated with MitraClip (April 2019-July 2020) were enrolled. The protocol of MR evaluation included: 2D and 3D color-Doppler (3D-vena contracta area- 3D-VCA), pulsed-wave Doppler (pulmonary vein- PV flow, stroke volume), continuous-wave Doppler (jet density), morphological parameters (spontaneous echocontrast) and invasive hemodynamic (mean left atrial pressure-LAP, V-wave) at baseline and after clip implantation. A multiparametric score (M-score) was calculated by including the significant predictors (3D-VCA, dense jet on CWD, final LAP, final V wave) of primary endpoint (CV death or HF related hospitalization) at one year follow-up, weighted according to the corresponding odds ratio, to predict the clinical outcome at one-month and one-year follow-up. Results. The final study population included 86 pts (mean age 78.3 +8.9yrs, 54.6% primary MR). Procedural success was achieved in 78 pts (90.7%). 3D-VCA (AUC 0.808) and current method for MR grading (AUC 0.801) were comparable predictors of lack of symptom improvement (<5 point change in KCCQ-OS score) at one-month (p = 0.398, DeLong's test). The M-score performed similarly as predictor of one-month follow-up but was a better predictor of primary endpoint at 1-year (AUC 0.919) compared to single parameters (p = 0.005 vs 3D-VCA DeLong"s test) and currently recommended methods for MR grading (p = 0.006 DeLong"s test). The optimal cut-off was 2 points with 86.7% sensitivity and 83.1% specificity. Conclusion. We evaluated intraprocedural TMVr result in a multiparametric approach showing that 3D-VCA alone is comparable to current recommended method for MR grading. However, the integration of echocardiographic and invasive hemodynamic parameters into a multiparametric score provided a further added value for predicting clinical outcome at one-year compared to currently recommended methods for MR grading and to 3D-VCA.